Curatives in the Old-Lithuanian Bible translations - Brudzyński, Paweł (Vilnius University Open Series, 2021)
The subject of the paper is curatives, a special type of causative verbs in Lithuanian, in the Bible translations by Johannes Bretke (1579–1590), Samuel Boguslaw Chylinski (1660), Samuel Bythner (1701), Philipp Ruhig (1727) and Juozapas Arnulfas Giedraitis (1816). Curatives are a special type of causation implementing the causee-suppressing valency (CSP) pattern. In the analyzed texts, one can notice several morphological, semantic or syntactic features coinciding with contemporary curative constructions. However, in addition to the morphology and semantics of curatives, the article discusses also some rare and interesting cases that can be interpreted as expressing the causee and includes remarks on the lexicalization processes.